1994
DOI: 10.1016/0014-5793(94)01115-x
|View full text |Cite
|
Sign up to set email alerts
|

Immunogold localization of glutathione transferase B1‐1 in Proteus mirabilis

Abstract: By using the immunolabelling technique, the cellular localization of glutathione transferase in Proteus mirabilis was investigated. Evidence was obtained indicating a signiticant higher content of glutathione transferase in the periplasmic than cytoplasmic space. This result further support the idea that bacterial glutathione transferase is involved in xenobiotic detoxication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
9

Relationship

8
1

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Studies on the interaction of PmGST B1-1 with a number of antimicrobial agents indicated that this enzyme was able to sequester antibiotics with avidity [14,16]. Indeed, our previous studies demonstrated the presence of PmGST B1-1 not only in the cytoplasm but also in the periplasmic compartment [37]. In addition, structural data indicate that there is a hydrophobic cavity large enough to bind an antibiotic molecule located at the dimer interface of the enzyme [18].…”
Section: Discussionmentioning
confidence: 95%
“…Studies on the interaction of PmGST B1-1 with a number of antimicrobial agents indicated that this enzyme was able to sequester antibiotics with avidity [14,16]. Indeed, our previous studies demonstrated the presence of PmGST B1-1 not only in the cytoplasm but also in the periplasmic compartment [37]. In addition, structural data indicate that there is a hydrophobic cavity large enough to bind an antibiotic molecule located at the dimer interface of the enzyme [18].…”
Section: Discussionmentioning
confidence: 95%
“…On the contrary, a high degree of specific labelling was detected for the bacteria grown in the presence of toxic 4-chlorophenol concentrations ( Fig. A predominant localisation of a GST species had already been observed in Proteus mirabilis [30]. Moreover, as shown in Fig.…”
Section: Localisation Of Gst and Msramentioning
confidence: 89%
“…Finally, crystallographic data highlighted the presence of a hydrophobic cavity large enough to bind antibacterial molecules located at the dimer interface [12]. These results were strengthened by the preponderant periplasmic location of the enzyme in the periplasmic space [81].…”
Section: Functionsmentioning
confidence: 99%